Processing and Waste Water Quality in Arya Duta Makassar Hotel - Ikram Hardi; Surya Mardani (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2015)
Based on the results of laboratory tests performed by a large hall occupational safety and health in 2013 (June-December) discovered that the Arya Duta Hotel waste water BOD levels as much as 77.813 mg / L, the COD as much as 129.688 mg / L, TSS as much as 72.8 mg / L with refer-ence to the Ministry of the Environment Decree No. 52 of 1995 on the effluent quality standards for hotel activity. This study aims to determine the Wastewater Treatment and Quality Liquid at Hotel Arya Duta Makassar in terms of the parameters pH, BOD, COD and TSS.This study is an observational study with descriptive design. The study population was all the result of the disposal of liquid waste Arya DutaMakassar hotel. Samples are Inlet and Outlet of the Waste Water Treatment Plant (WWTP). Grab sampling technique that sampling where the sam-pling at a certain time is 08.02 hours in the morning and afternoon at 15:00. Liquid waste water samples are taken at Hotel Arya Duta Makassar tested in the laboratory Polytechnic Makassar Health Department Environmental Health. Measurement results are then analyzed descriptively.Research shows that there are still parameters that exceed the quality standards that are not in accordance with the Decree of the Minister of Environment No. 52 of 1995 on the Liquid Waste Quality Standards for Activities Hotel. On average pH Inlet as much as 7.25 and an average outlet pH levels as much as 5.08. On average Inlet BOD as much as 237.79 mg / L and for the aver-age Outlet BOD as much as 33.69 mg / L. On average Inlet COD concentration of 400 mg / L and for the average Outlet COD content of 160 mg / L. On average Inlet TSS levels as much as 0,026 mg / L and for the average Outlet TSS levels as much as 0,015 mg / L and the processing is done four times stages: Preliminary treatment, primary treatment, secondary treatment, and Tertiary treatment.Recommended to the hotel to clean wastewater treatment so that the dirt that still contain harmful chemicals, grease, and detergents can be reduced.Keyword : Wastewater, Hotel, pH, BOD, COD, TSS, and Processing